2001
DOI: 10.1093/jexbot/52.362.1761
|View full text |Cite
|
Sign up to set email alerts
|

The export of amino acid in the phloem is altered in wheat plants lacking the short arm of chromosome 7B

Abstract: Grain protein content is one of the major determinants of the baking and nutritional quality of wheat. It has previously been reported that the ditelosomic line of wheat (Triticum aestivum L.) CSDT7BL, where the short arm of chromosome 7B is missing, shows a lower grain protein concentration than the normal line, but a similar grain yield. In the present paper the growth and nitrogen (N) metabolism of wheat plants cv. Chinese Spring (CS) and its ditelosomic line CSDT7BL were compared. When plants were grown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The leaf proteins, mostly Rubisco, are hydrolysed to amino acids during senescence by proteolytic enzymes, and are then exported to the phloem (Ho¨rtensteiner and Feller 2002). It has been shown that GPC is related to the soluble amino acids in the flag leaf (Barneix and Guitman 1993) and to the amount of amino acids exported to the phloem (Caputo et al 2001). The present experiments showed for the first time that at anthesis the flag leaves of the RSL no.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf proteins, mostly Rubisco, are hydrolysed to amino acids during senescence by proteolytic enzymes, and are then exported to the phloem (Ho¨rtensteiner and Feller 2002). It has been shown that GPC is related to the soluble amino acids in the flag leaf (Barneix and Guitman 1993) and to the amount of amino acids exported to the phloem (Caputo et al 2001). The present experiments showed for the first time that at anthesis the flag leaves of the RSL no.…”
Section: Discussionmentioning
confidence: 99%
“…The major phloem‐exported amino acid in barley and wheat is glutamate, followed by varying levels of aspartate, glutamine, threonine and serine (Winter et al. 1992; Caputo et al. 2001; Kichey et al.…”
Section: Nitrogen Metabolism and Re‐translocationmentioning
confidence: 99%
“…Free amino acids are exported via the phloem to the developing grain, either directly or indirectly via the root or the glumes (Simpson et al 1983). The major phloem-exported amino acid in barley and wheat is glutamate, followed by varying levels of aspartate, glutamine, threonine and serine (Winter et al 1992;Caputo et al 2001;Kichey et al 2006). Thus, glutamate, originating in 2-oxoglutarate, plays a central role in the remobilisation of nitrogen (Forde & Lea 2007).…”
Section: Nitrogen Metabolism and Re-translocationmentioning
confidence: 99%
“…A gene for high GPC has been proposed in chromosome 5D (Turner et al, 2004), and a putative gene affecting GPC has been located in the short arm of chromosome 7B of wheat cv. Chinese Spring (Barneix et al, 1998;Caputo et al, 2001). Recombinant substitution lines derived from a substitution line of chromosome 6B from Triticum turgidum L. var.…”
Section: Wheat Baking Properties and Grain Proteinmentioning
confidence: 99%
“…The final GPC has been correlated with the free amino acid concentrations in the flag leaf during grain filling (Millet et al, 1992;Barneix and Guitman, 1993), and it has been shown that the ditelosomic line of wheat Chinese Spring CSDT7BL that is deficient in the export of several amino acids to the phloem also shows a decreased GPC compared to the normal line (Caputo et al, 2001). It has also been shown that the high GPC lines of T. turgidum L. var.…”
Section: Source Regulation Of Grain Protein Accumulationmentioning
confidence: 99%